SYSTEMIC LINGUISTIC ANALYSIS OF TEXT APPRAISAL ON STUDENTS’THESES WRITING IN ENGLISH - Magdalena Ngongo (LITERA : Jurnal Bahasa Dan Sastra, 2016)
ABSTRACT This paper is aimed to describe text appraisal of thesis writing, as one of the requirements tofulfil undergraduate degree of English teaching. There are 10 English theses writing taken to beanalyzed qualitatively. These theses are written by undergraduate students who got „A‟ grade intheir theses examination. Based on the analysis, it was found out that in thesis writing, text appraisal employed covers three types of attitude, namely affect, appreciation and judgments. Inaddition graduation and engagement can be also included in language evaluation in whichengagement is the most used. Referring to the attitude, judgment is more used than affect andappreciation. This fact indicates that the students‟ theses  writing more personal and emotionalthan appreciative. Engagement was also most used than graduation. This fact indicates thatundergraduate students make use of types  of  expand namely,  entertain as  well  as attribute,whereas in graduation they more concerned for intensification and quantification and had very limited concerns or even ignored the use of sharpening and softening resource. This fact mightsuggest that students should be taught and trained more relating to writing, such as academicwriting that specifying in evaluating language.  Keywords: text appraisal, theses writing, systemic  ABSTRAK Tulisan ini bertujuan untuk mendeskripsikan penilaian teks penulisan skripsi, sebagai salah satusyarat untuk memenuhi gelar sarjana mengajar bahasa Inggris. Ada 10 skripsi dalam BahasaInggris dianalisis secara kualitatif. Skripsi ini ditulis oleh mahasiswa yang mendapat nilai 'A' dalam ujian skripsi mereka. Berdasarkan analisis, ditemukan bahwa dalam penulisan skripsi,teks penilaian yang digunakan mencakup tiga jenis sikap, yaitu mempengaruhi, penghargaandan penilaian. Evaluasi bahasa yang paling digunakan. Mengacu kepada sikap, penilaian lebihdigunakan daripada pengaruh dan penghargaan. Fakta ini menunjukkan bahwa skripsimahasiswa ditulis dengan lebih pribadi dan emosional. Keterlibatan juga paling seringdigunakan daripada kelulusan. Fakta ini menunjukkan bahwa mahasiswa menggunakan jenismemperluas sedangkan dalam kelulusan mereka lebih cenderung untuk intensifikasi dan kuantifikasi dan memiliki perhatian yang sangat terbatas atau bahkan mengabaikan penggunaan                                                                                                                          sumber daya. Fakta ini mungkin menunjukkan bahwa siswa harus diajarkan dan dilatih lebihlanjut berkenaan dengan cara menulis, seperti menulis akademik yang menentukan dalammengevaluasi bahasa. Kata kunci: appraisal teks, penulisan skripsi, sistemik